Tris(pentafluorophenyl)borane‐Catalyzed Functionalization of Benzylic C−F Bonds - Hoppe, Axel; Stepen, Arne J.; Köring, Laura; Paradies, Jan (Advanced Synthesis & Catalysis)
Abstract The activation of C( sp 3 )−F bonds by the commercially available catalyst B(C 6 F 5 ) 3 is reported and applied in reactions with arenes, allylic, vinylic and acetylenic silanes, and olefins to achieve a variety of C−C bond formations (45 examples).
Keywords: fluoride; bond activation; borane; Lewis acid; C-C bond formation

Hydrogel-Based Biosensors - Völlmecke, Katharina; Afroz, Rowshon; Bierbach, Sascha; Brenker, Lee Josephine; Frücht, Sebastian; Glass, Alexandra; Giebelhaus, Ryland; Hoppe, Axel; Kanemaru, Karen; Lazarek, Michal; Rabbe, Lukas; Song, Longfei; et al. (Gels)
There is an increasing interest in sensing applications for a variety of analytes in aqueous environments, as conventional methods do not work reliably under humid conditions or they require complex equipment with experienced operators. Hydrogel sensors are easy to fabricate, are incredibly sensitive, and have broad dynamic ranges. Experiments on their robustness, reliability, and reusability have indicated the possible long-term applications of these systems in a variety of fields, including disease diagnosis, detection of pharmaceuticals, and in environmental testing. It is possible to produce hydrogels, which, upon sensing a specific analyte, can adsorb it onto their 3D-structure and can therefore be used to remove them from a given environment. High specificity can be obtained by using molecularly imprinted polymers. Typical detection principles involve optical methods including fluorescence and chemiluminescence, and volume changes in colloidal photonic crystals, as well as electrochemical methods. Here, we explore the current research utilizing hydrogel-based sensors in three main areas: (1) biomedical applications, (2) for detecting and quantifying pharmaceuticals of interest, and (3) detecting and quantifying environmental contaminants in aqueous environments.

Frustrated Lewis Pair‐Catalyzed Hydroboration of Nitriles: FLP Versus Borenium Catalysis - Sieland, Benedikt; Hoppe, Axel; Stepen, Arne J.; Paradies, Jan (Advanced Synthesis & Catalysis)
Abstract A frustrated Lewis pair‐catalyzed hydroboration of aromatic and aliphatic nitriles was developed. The catalyst provides the primary amines in high yields of 77–99% with catalyst loading as low as 2 mol%. The reaction displays high functional group tolerance towards esters, amides, nitro groups and aliphatic halides. The addition of the diborylated amines to ethyl 3‐phenylpropiolate proceeds with Z‐selectivity with d.r. of >99:1 in 77–90% yield over two steps. The reaction mechanism was investigated by control and computational experiments. magnified image
Keywords: hydroboration; nitrile; amine; frustrated Lewis pair; density functional theory

Backbone-Degradable (Co-)Polymers for Light-Triggered Drug Delivery - Rust, Tarik; Jung, Dimitri; Hoppe, Axel; Schoppa, Timo; Langer, Klaus; Kuckling, Dirk (ACS Applied Polymer Materials)
Keywords: backbone-degradable; light-responsive; redox-responsive; drug delivery; nanoparticles